Implementasi PAK Kepada Remaja Melalui Media Penyiaran Radio Mitra Kawanua di Jemaat GMIM Petra Ranomuut Manado - Pinontoan, Devis O. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to determine the implementation of PAK to teenagers through spiritual radio broadcasting media. This research is qualitative research Data was collected through observatio and literature review. From the results of the analysis and interpretation of the data, indications were obtained that the implementation or application of Christian Religious Education to teenagers today is very necessary to mature their faith and direct them to live pleasingly and grow in Christ.From the results of these findings, it is recommended that teenagers, parents, church organizations or church leaders and the government can utilize spiritual radio broadcasting media in implementing PAK